(untitled) (Analele Universității București. Limba și literatură română, 2025)
The long history of debates on the topic provides a wealth of information on the first attestations, the semantics, the lexical productivity, the dialectal spread, the onomastic transfer, and the origin of the Romanian term buză (Engl. ‘lip’; ‘edge’; ‘river bank’), information which is unfortunately scattered in various journal articles that are not easy to access. The aim of the paper is to give an overview of the existing studies on the Romanian lexeme buză, to highlight the most relevant conclusions, and to make brief comments wherever we consider it necessary.